2015
DOI: 10.1007/s11661-015-2916-2
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanism of Decrease of Impact Toughness in Coarse-Grain Heat-Affected Zone of HSLA Steel with Increasing Welding Heat Input

Abstract: This paper analyzes the micromechanism of decrease of impact toughness with increasing the welding heat input in coarse-grain heat-affected zone (CGHAZ) of a low-alloy high-strength ship-building steel plate. By comparing the microstructures, measuring the extending length of the fibrous crack, identifying the critical event of cleavage fracture, measuring the critical length, and calculating the local cleavage fracture stress r f , and then using the basic principles of the micromechanism of cleavage fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…A coarse grain has a smaller crystal interface and the grain boundary is straight. In addition, cracks propagate and develop easily, which is harmful to the strength and toughness [30]. For sample JT-2, the average grain diameter of FP2 was 119 µm, which had the worst toughness.…”
Section: Grain Sizementioning
confidence: 99%
“…A coarse grain has a smaller crystal interface and the grain boundary is straight. In addition, cracks propagate and develop easily, which is harmful to the strength and toughness [30]. For sample JT-2, the average grain diameter of FP2 was 119 µm, which had the worst toughness.…”
Section: Grain Sizementioning
confidence: 99%
“…The impact energy is increased nearly by 3 times from 34 J to 123 J when the grain size was refined from 24 μm to 13 μm, indicating that grain refinement contributes largely to the toughness of the steel. The effect of grain refinement on the toughness of the steel can be explained by the generalized Griffith's equation given below [31][32][33].…”
Section: 3 Mechanical Propertiesmentioning
confidence: 99%
“…It was observed that the average bainitic packet size became smaller from the FL to the FGHAZ in the CGHAZ produced by SAW. Since the heat input of the SAW process was higher than that of the FCAW process [32], the average bainitic packet size in Figure 6c is about 200 μm, which is bigger than the size of 100 μm seen in Figure 5c. In the case of the control-rolled steel, it is known that the martensite/austenite constituent (MA) is generated due to the welding heat depending on the amount of carbon in the steel when the upper bainite structure is formed [33][34][35].…”
Section: Microstructure Analysismentioning
confidence: 80%